Mounting fears - Woods, Stuart (Holly Barker, 2009)
President Will Lee is having a rough week. His vice president just died during surgery. Confirmation hearings for the new vice president are under way, but the squeaky-clean governor whom Will has nominated may have a few previously unnoticed skeletons in his closet. And Teddy Fay, the rogue CIA agent last seen in Shoot Him If He Runs, is plotting his revenge on CIA director Kate Rule Lee - the president's wife. Plus there are some loose nukes in Pakistan that might just trigger World War III if Will's diplomatic efforts fall short. It's up to President Lee - with some help from Holly Barker, Lance Cabot, and a few other Stuart Woods series regulars - to save the world, and the upcoming election.